The Department of Education and Culture's Strategy to Address Educator Shortage in Pontianak - Rahmawati Sururama; Valentino Christ Vowel (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this research was to examine the Department of Education and Culture's strategy for addressing the city of Pontianak's teacher shortage. This study employs an inductive descriptive qualitative method. Data reduction methods, data display/data presentation, and conclusion drawing/verification were used to analyze the collected data. In order to gather the data, we used a combination of observation, documentation, and in-depth interviews as data collection techniques. Structured interviews and purposive sampling were used to select participants for the study. Research shows that the Department of Education and Culture's strategy for dealing with the shortage of teachers is adequate. There is no doubt that the Department of Education and Culture is doing everything it can to alleviate the shortage of teachers in Pontianak City, whether it's through policies like hiring PPPK employees or stipulating that ASN be formed exclusively for educators.